Energy modelling in the South African electric power industry - Ben-Yaacov, Giora Zeev (Department of Mechanical Engineering, 2023)
The subject of this thesis is the development of a modelling system for the planning of the South African electricity supply industry. A power system planning process was developed with the object of ~stablishing a long-range development plan that would enable the selection and timing of individual projects. This planning process is represented by several sub-models which include the prediction of future demands, the assessment of the generating capacity and the proportions of the different types of generating plant on the system (the plant "mix"), the analysis of the transmission network performances and the simulation of the financial processes. One of the characteristics of the modelling system presented is its three-stage structure. The first stage is represented by the load model for the long-term prediction of power and energy demand. The second stage is represented by the two expansion models for generation and transmission. With the aid of these two models several expansion strategies are pre-selected, and then in the third stage, using the financial model, the total capital requirements are established. The future system demand is predicted from the analysis of historical data and by the formulation of the electricity - and economic growth relationship: Two major calculations, linear programming optimisation and loss of load probability analysis, are used in the computer models which aid the policy makers in selecting the optimum size and mix of the generating plants and scheduling the operation and maintenance of the generating units. Transmission system analysis programs have been developed in such a way that they use a common power system data base which enables the planning engineers to store and maintain their power system data. The calculation routines include load flow, fault analysis, stability studies, single and three phase travelling. Waves, and power and high ii frequency transmission line parameters. The costing and financial models include the analysis of costs of all new expansion equipment, the costs of operation and maintenance of the generation units, transmission equipment and fuel, and the simulation of the financial environment and accounting processes. On the basis of experience gained so far, the author arrives at the conclusion that the modelling system presented is capable of providing a useful tool for planning the expansion of the South African electricity supply industry .